Metamorphic proteins at the basis of human autophagy initiation and lipid transfer - Nguyen, Anh; Lugarini, Francesca; David, Céline; Hosnani, Pouya; Alagöz, Çağla; Friedrich, Annabelle; Schlütermann, David; Knotkova, Barbora; Patel, Anoshi; Parfentev, Iwan; Urlaub, Henning; Meinecke, Michael; et al. (Molecular cell, 2023)
Autophagy is a conserved intracellular degradation pathway that generates de novo double-membrane autophagosomes to target a wide range of material for lysosomal degradation. In multicellular organisms, autophagy initiation requires the timely assembly of a contact site between the ER and the nascent autophagosome. Here, we report the in vitro reconstitution of a full-length seven-subunit human autophagy initiation supercomplex built on a core complex of ATG13-101 and ATG9. Assembly of this core complex requires the rare ability of ATG13 and ATG101 to switch between distinct folds. The slow spontaneous metamorphic conversion is rate limiting for the self-assembly of the supercomplex. The interaction of the core complex with ATG2-WIPI4 enhances tethering of membrane vesicles and accelerates lipid transfer of ATG2 by both ATG9 and ATG13-101. Our work uncovers the molecular basis of the contact site and its assembly mechanisms imposed by the metamorphosis of ATG13-101 to regulate autophagosome biogenesis in space and time.